2017
DOI: 10.1039/c6cp07198h
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-functionalized semiconductor surfaces: strong surface electronic effects from minor alterations to backbone composition

Abstract: The use of non-canonical amino acids is a powerful way to control protein structure. Here, we show that subtle changes to backbone composition affect the ability of a dipeptide to modify solid surface electronic properties. The extreme sensitivity of the interactions to the peptide structure suggests potential applications in improving the performance of electronic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…For example, X-ray photoelectron spectroscopy data for GaAs with water reveals shift in the As 2p due to the formation of As-H 36 . In a separate study, the FTIR peak assigned to the amino group is found shifted due to its adsorption at the GaAs surface 37 . Therefore, cross-correlation between the differential conduction of the bare Schottky GaAs and those of the diode in contact with the amino acids can quantify the modification to the GaAs chemisorption.…”
Section: Ongoing and Future Workmentioning
confidence: 86%
“…For example, X-ray photoelectron spectroscopy data for GaAs with water reveals shift in the As 2p due to the formation of As-H 36 . In a separate study, the FTIR peak assigned to the amino group is found shifted due to its adsorption at the GaAs surface 37 . Therefore, cross-correlation between the differential conduction of the bare Schottky GaAs and those of the diode in contact with the amino acids can quantify the modification to the GaAs chemisorption.…”
Section: Ongoing and Future Workmentioning
confidence: 86%
“…This study emphasized the important role of peptides as tools for improving the electronic properties of FET. [ 318 ] Mehlhose et al synthesized novel helical peptides based on (Leu‐Aib)n sequences that were chemically coupled to gallium nitride (GaN) surfaces. GaN exhibited good electrochemical stability over a wide frequency window, and the controllable electronic properties made it possible to fabricate various heterostructures.…”
Section: Applications Of Peptide‐based Bioelectronic Materials and De...mentioning
confidence: 99%
“…[8][9][10][11][12] Accordingly, significant efforts were devoted to reveal the effects of peptide adlayers on the surface work function of metals and semiconductors. [13][14][15][16][17][18] The surface work function was found to be affected by the nature of the amino acids 13 and by their position in the peptide sequence, 14 as well as the structure of the peptide backbone. 15 The applicability of this approach was demonstrated through the incorporation of basic amino acids in the sequence of short peptide functionalization layers to reduce the work function of transparent conductive oxides and graphene in order to improve their performance as a cathode for a device.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] The surface work function was found to be affected by the nature of the amino acids 13 and by their position in the peptide sequence, 14 as well as the structure of the peptide backbone. 15 The applicability of this approach was demonstrated through the incorporation of basic amino acids in the sequence of short peptide functionalization layers to reduce the work function of transparent conductive oxides and graphene in order to improve their performance as a cathode for a device. 8,[16][17][18][19][20] However, to the best of our knowledge, the influence of multivalent interactions on the surface electronic properties, and the work function in particular, has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%